Carbon Solving Carbon's Problems: Recent Progress of Nanostructured Carbon‐Based Catalysts for the Electrochemical Reduction of CO2. Issue 21 (18th July 2017) - Vasileff, Anthony; Zheng, Yao; Qiao, Shi Zhang
Abstract: The electrochemical reduction of CO2 to useful molecules offers an elegant technological solution to current energy security and sustainability issues because it sequesters carbon from the atmosphere, provides an energy storage solution for intermittent renewable sources, and can be used to produce fuels and industrial chemicals. Nanostructured carbon materials have been extensively used to catalyse some key electrochemical processes because of their excellent electrical conductivity, chemical stability, and abundant active sites. This progress report focuses on nanostructured carbon materials, namely graphene materials, carbon nanotubes, porphyrin materials, nanodiamond, and glassy carbon, which have recently shown promise as high performing CO2 reduction electrocatalysts and supports. Along with discussion regarding materials synthesis, structural characterisation, and electrochemical performance characterisation techniques used, this report will discuss the findings of recent computational CO2 RR studies which have been key to elucidating active sites and reaction mechanisms, and developing strategies to break conventional scaling relationships. Lastly, challenges and future perspective of these carbon‐based materials for CO2 reduction applications will be given. Much work is still required to realise the commercial viability of the technology, but advanced experimental techniques coupled with theoretical calculations are expected to facilitate future development of the technology. Abstract : Carbon nanostructures, such as graphene and carbon nanotubes, provide many advantages to the electrocatalytic reduction of CO2 . Their unique structures allow for chemical and morphological tailoring of active sites and anchoring of active nanoparticles for enhanced CO2 reduction activity. Further development of these materials coupled with computational techniques will support efforts to develop commercially viable clean energy storage devices.